TIS Toruński Informator "Solidarności" . no. 226, 1989 - Cichoń, Wiesław; Spandowski, Roman; Kaczor, Andrzej; Sienkiewicz, Radek; Borek, Piotr; Musielak, Ryszard (s.n.], 1989)
Creation and circulation: From issue no. 10=227(1989)published legally